2015
DOI: 10.1123/ijspp.2014-0222
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Physical Capacities Between Nonselected and Selected Elite Male Competitive Surfers for the National Junior Team

Abstract: All performance variables, particularly CMJ height; time to 5-, 10-, and 15-m sprint paddle; sprint paddle PV; time to 400 m; and endurance paddling velocity, can effectively discriminate between S and NS competitive surfers, and this may be important for athlete profiling and training-program design.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
46
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(49 citation statements)
references
References 14 publications
1
46
0
Order By: Relevance
“…Given that in this study the participants were high-level young gymnasts, even borderline differences that have a moderate effect size may be "practically significant" in providing useful information for the training and selection process (Tran et al, 2015). Standing and balancing on the ball of the foot requires a correct body posture, body alignment and a stable ‘releve’ position.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that in this study the participants were high-level young gymnasts, even borderline differences that have a moderate effect size may be "practically significant" in providing useful information for the training and selection process (Tran et al, 2015). Standing and balancing on the ball of the foot requires a correct body posture, body alignment and a stable ‘releve’ position.…”
Section: Discussionmentioning
confidence: 99%
“…Correct technical execution is at the same time a demand for success and a prerequisite for future technical development. In that aspect, physical fitness forms the basis of technical skill development in youth sports (Faigenbaum et al, 2009; Lloyd and Oliver, 2014) while a higher level of physical fitness is often related to a higher level of performance (Piazza et al, 2014; Tran et al, 2015). Therefore, the purpose of the present study was to examine the association between selected physical fitness variables and the technical execution score in young rhythmic gymnasts varying in the performance level.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, bodyboarding scoring potential places strong emphasis on aerial manoeuvres on bigger and heavier sections of waves (Surfing Australia, 2017). In order to undertake complex high-risk manoeuvres in such situations, high technique levels are required and whole-body strength and power characteristics needed to tolerate the physical demands of such movements (Tran et al, 2015) and landings.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, greater physical qualities [e.g., strength and power] have been reported to associate with surfing performance [28,30]. Recent evidence revealed physical performance reflected selection from a group of elite junior surfers to represent Surfing Australia National Junior Team at the International Surfing Association World Junior Surfing Championship [33]. Collectively, these studies demonstrated the importance of physical qualities for surfing performance and using a group of junior surfers distinguished physical performance among selected and non-selected elite junior surfers.…”
Section: Introductionmentioning
confidence: 99%